Hyphenated voices: The organization of racialized subjects in contemporary Danish public debate - Christensen, Jannick Friis; Just, Sine N.; Muhr, Sara Louise (Organization (London, England), 2022)
Applying a conceptual framework of hyphenation, understood as the organization of racialized subjects, this paper investigates rhetorical strategies for working existing hyphens as practiced within an Action Aid Denmark initiative to train young people to become public opinion leaders in anti-discrimination matters. We identify three such rhetorical strategies: (1) Silencing: Racialized subjects are organized by majority voices that speak of/for ‘the Other’; the training explicitly seeks to change the organization of public debate by working this hyphen. (2) Positioning: The main strategy for working the hyphen, as taught in the course, is to speak from a minority position, but in a manner that is recognizable to the majority. Thus, non-white participants are trained to speak with white voice; they become exceptions to the rule, tokens or role models when telling their stories in a scripted manner. And (3) Representing: In telling their own stories, the aspiring opinion leaders come to speak for racialized subjects as a group. Thus, the course (unwittingly) reproduces the current racialized organization of public space in the form of ‘benign discrimination’. On the basis of this analysis, the article advances postcolonial organization studies by demonstrating that hyphenation cannot be overcome, but must be engaged in a continuous process of re-working the hyphen. Thus, the task of researchers and practitioners alike is to show the constraints of current hyphenations and find strategies for organizing subjects in more equal and open relations.